Investing into the abyss: The continued misclassification of multi-sector managed funds - Watson, John R (Institutional Knowledge at Singapore Management University, 2010)
The objective of this paper is to assess whether Australian multi-sector managed funds are misclassified, and then, having found this to be the case, determine if this misclassification has any impact on fund performance. We adopt a strong form of returns based style analysis to investigate a monthly sample of Australian multi-sector funds over the five-year sample period 2003:04-2008:03. The evidence provided demonstrates that insufficient attention has been paid as to whether fund managers are able to keep within their tactical asset allocation ranges and presents that misclassification exist for Australian multi-sector managed funds but that the effect on fund performance is not significant. The paper adds to the literature by demonstrating that no association exists between misclassification and fund performance.